Necesidad de Reformar el Código Orgánico Integral Penal, el Art. 385 para que se sustituya la sanción de Privación de Libertad por Trabajos Comunitarios, en el caso de Personas que desarrollen Actividad Laboral bajo relación de dependencia en el sector Público o Privado - Melgar Montaño, Marina Fernanda (2016)
The purpose of this research is to present a proposal on "community work in contravention of driving a vehicle while intoxicated by persons performing labor activity in the public or private sector," avoiding be punished with deprivation of freedom to not lose their jobs, emphasizing sanctions as provided by law, in which states among others the "community work" is an interesting topic so it is thought desirable to sensitize the people who committed this violation of sanction with work to benefit the community, to repair the damage done to society in general, as a violation of culpable character, should replace the penalty, as long as the offender has not caused accident and is not a recidivist in such contraventions, it is necessary to make known to the general public what the sanctions to be applied exceptionally well in this type of contraventions to be informed that an offender who is a repeat offender may not apply for community service as punishment will be, but should fulfill his punishment according as stated in Article 385 in numerals 1-2 and 3 of the scale in the commission of the offense. What it was tested positively by the application of methods and techniques of scientific, that guided me to achieve results, which helped support the law reform proposal. The theoretical and field of this thesis work allowed me to obtain criteria, scientific and methodological level with clear and precise grounds on the replacement of imprisonment for violation of Article 385 of the COIP, where offenders they may request the replacement of its sanction. Also the well known literature contributed to the verification of goals, and testing of the hypotheses, enabling support the proposed changes. Finally I consider necessary and important and that it is both Assemblymen and society as a whole, take responsibility to move towards a fully fair, balanced and harmonious society based on knowledge about the implementation of this sanction for offenders justifying found employment relations, avoiding overcrowding in prisons and job losses, and that this violation not remain unfulfilled its sanction that should be enshrined in our Constitution and Criminal Law.